Pseudo scapula alata: a case report of a scapular osteochondroma - Sousa, Rita M.; Sapage, Rita; Branco, Carlos; Sousa, Diogo; Reis, Joao; Geraldes, Ricardo; Branco, Ricardo; Cruz, António Gomes (International Journal of Research in Orthopaedics, 2020)
An osteochondroma is a type of cartilaginous tumour, that frequently affects long bones. In the scapula, although rare, this benign tumour is the most frequently encountered. The symptoms at this location are usually related to the mass effect that it can produce. Surgery is recommended when symptoms of compression, pain or an increase in size are noticed. The authors present a case of a 11 year-old-boy with an osteochondroma on the ventral surface of the scapula, that cause a pseudo winging of this bone and pain, with indication for surgical excision. Pseudo scapula alata should be differentiated from the true one, which is a dynamic dyskinesia. In the presence of this static deformity the surgeon must keep in mind other diagnosis as a scapular osteochondroma or other mass effect lesions. This benign tumour does not frequently suffer malignant transformation. Surgery can lead to a complete resolution of the symptoms, and if done properly decrease to almost zero the rate of recurrence. The diagnosis of the tumour in this location can be delayed due to its atypical location and presentation. With this case report the authors expect to raise awareness of the unusual manifestations of osteochondroma, especially in the paediatric setting.